2017
DOI: 10.1016/j.cobeha.2017.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Models of spatial and temporal dimensions of memory

Abstract: Episodic memory involves coding of the spatial location and time of individual events. Coding of space and time is also relevant to working memory, spatial navigation, and the disambiguation of overlapping memory representations. Neurophysiological data demonstrate that neuronal activity codes the current, past and future location of an animal as well as temporal intervals within a task. Models have addressed how neural coding of space and time for memory function could arise, with both dimensions coded by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 91 publications
(152 reference statements)
0
10
0
Order By: Relevance
“…The prevailing interpretation of these distortions has been that a rescaled environment induces a rescaled version of the cognitive map [10,12,14,16,18,22,29,37,39,41,45]. Our results suggest an alternative interpretation.…”
Section: Discussionmentioning
confidence: 49%
“…The prevailing interpretation of these distortions has been that a rescaled environment induces a rescaled version of the cognitive map [10,12,14,16,18,22,29,37,39,41,45]. Our results suggest an alternative interpretation.…”
Section: Discussionmentioning
confidence: 49%
“…Oscillatory interference models of path integration hypothesize that the slope of the theta frequency versus running speed correlation reflects the presence of velocity-controlled oscillators whose frequencies increase with running speed (Burgess, 2008). Computational models suggest a possible role of cholinergic modulation in coding of novelty, spatial location, and running speed in the entorhinal cortex (Hasselmo et al, 2017). The y-intercept of the theta frequency versus running speed relationship is affected by anxiolytic drugs (Wells et al, 2013;Monaghan et al, 2017), whereas environmental novelty (Wells et al, 2013) and muscarinic cholinergic signaling (Newman et al, 2013) have been shown to specifically affect the slope of the theta frequency to running speed relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Recent neuroimaging experiments suggest that different aspects of complex scenes can be represented concurrently, such as the fine-grained information about the color of objects embedded within scenes (Richter et al, 2016). Moreover, fine-and coarse-grained detail about complex scenes are represented within the medial temporal lobes and prefrontal cortex (Cooper & Ritchey, 2019;Kolarik, Baer, Shahlaie, Yonelinas, & Ekstrom, 2018;Nilakantan, Bridge, VanHaerents, & Voss, 2018;Stevenson et al, 2018;Yonelinas, 2013), perhaps modulated by differences in the neural dynamics associated with fineand coarse-grained spatial information (Brunec, Moscovitch, & Barense, 2018;Bush, Barry, & Burgess, 2014;Collin, Millivojevic, & Doeller, 2015;Hasselmo et al, 2017;Poppenk, Evensmoen, Moscovitch, & Nadel, 2013). In one task, participants reconstructed the color, orientation, and spatial position associated with real-world objects studied on a 2D circle (Richter et al, 2016).…”
Section: Discussionmentioning
confidence: 99%